Evaluación clínica del paciente con síntomas del tracto urinario inferior - Valdevenito S., Juan Pablo; Álvarez O., Diego; Kobus G., Cristóbal; Bull C., Leonardo (Revista Hospital Clínico Universidad de Chile, 2016)
Lower urinary tract symptoms are divided into three groups, storage, voiding and postmicturition symptoms. Their level of agreement with urodynamic investigation is poor. Clinicalhistory should be complemented by the application of validated symptom questionnairesand the recording of urinary events. Here we refer to: a) the International Consultation onIncontinence Questionnaire, Short Form (ICIQ-SF), b) the Urogenital Distress Inventory - ShortForm (UDI-6) and Incontinence Impact Questionnaire – Short Form (IIQ-7), c) the urinaryincontinence Severity Index and d) the American Urological Association Symptom Index. Therecordings of urinary events can be done in three main forms: a) micturition time chart, b)frequency volume chart, and c) bladder diary. The International Consultation on IncontinenceQuestionnaire bladder diary (ICIQ bladder diary) is the only one validated. Physical exam shouldinclude abdominal and genital examination, covering pelvic organ prolapse quantification inwomen, prostate evaluation in men, pelvic floor muscle function evaluation in both genders, anda neurologic examination focused on evaluation of the sacral nerves. It is useful to supplementthe physical examination with the evaluation of the mobility of the bladder neck and proximalurethra through the Q-tip test, and with the quantification of urine leakage through the pad test